TERMS OF TRADE, TRADE RESTRICTIONS AND REAL EXCHANGE RATE IN NIGERIA - JONGBO, OLAJIDE CLEMENT (Annals of Spiru Haret University. Economic Series, 2022)
This study examined the determinants of the real exchange rate in Nigeria. To achieve the stated objectives, several empirical tests were conducted to ascertain the relationship among the variables under study. They include the descriptive statistics test, the ADF unit root test, the serial correlation and stability tests, the ARDL bound test and ARDL short-run ECM test as well as the cointegration test. Analyses of the results revealed that real government expenditure has a negative but significant relationship with the real exchange rate. Both domestic money supply and nominal exchange rate both have a positive and significant relationship with the real exchange rate. The results further revealed that real trade restrictions and technological progress both have a positive but insignificant impact on the real exchange rates. In conclusion, both real and nominal variables are the core fundamentals that determined the real exchange rate in Nigeria mostly in the short run. Consequently, the study recommended that regarding the real terms of trade; since capital accumulation appreciates the real effective exchange rate, there is a need for the creation of enabling environment that encourages investment in the tradable goods sector, rather than the non-tradable goods sector.